Use of the Beam Analogy Approach to Predict the Ultimate Shear Strength of Prestressed Flat Slab (2012)
The aim of the study was to predict the ultimate shear strength of a prestressed flat slab at the slab-column junction using the beam analogy approach. The beam analogy method, with other shear strength prediction methods such as the methods proposed by Hawkins, ACI 318-02, CSA A23.3-2004 were studied. The results were compared with the BS Code results to determine the variation in shear strength values. The approach employed a hypothetical flat slab layout, which was analyzed and designed for shear using all the various approaches while considering centre, edge and corner conditions. Values of the shear capacity were obtained using spreadsheet by varying the depth of the slab, and the area of the column. The values of the shear capacity of all the four methods were compared with the BS 8110. The results showed that there was a close relationship between the beam analogy approach and the BS 8110 method of shear strength prediction. As the depth of the slab increased, the beam analogy method was found to be more conservative, and as expected, the concrete shear stress at the slabcolumn junction reduced with increase in slab depth, which is the same depth for the idealized beam. Also, as the column area increased, while other parameters held constant, the shear strength at the junction was fortified. Also increasing the column area gave a closer relationship between the beam analogy approach and the BS Code than increasing the slab depth.